Anton Vovk – kanonik (1940–1945) - Otrin, Blaž (Acta ecclesiastica Sloveniae, 2024)
In 1940, Bishop Rožman appointed Anton Vovk canon of the Ljubljana Cathedral chapter. He had intended to appoint him the new rector of the theological seminary already in the 1941/42 academic year, but due to the beginning of the Second World War, this was moved to 1944. During the war, Vovk performed numerous duties and was a loyal and active bishop’s assistant, but he was engaged most of all in helping numerous refugee priests who found themselves in the Ljubljana region. He did not declare himself on either of the hostile sides in the civil war during the war, although he did strongly condemn and reject communism. Bishop Rožman also entrusted him with the task of recon ciliation between priests of the opposing sides, in which endeavour he was unfortunately not successful. He enjoyed the trust of all except the occupier with whom he had no contact. At the end of the war, he was greatly disappointed due to the fact that almost every seminary theologian went abroad, while in the weeks just after the end of the war, he also experienced the chaos and threats of the new authorities.
Keywords: begunci; druga svetovna vojna; Ljubljana cathedral chapter; ljubljanski stolni kapitelj; refugees; Rožman, Gregorij; Second World War; Vovk, Anton